Predictors of emergency cesarean section in women with preexisting diabetes. (May 2020) - Fischer, Margit B.; Vestgaard, Marianne; Ásbjörnsdóttir, Björg; Mathiesen, Elisabeth R.; Damm, Peter
Highlights: Eighty percent of women planned a vaginal delivery with a success rate of 65 %. Birth weight was similar between vaginal and emergency cesarean section deliveries. Predictors of emergency cesarean section were similar to the background population. Ultrasonic estimated fetal size did not predict emergency cesarean section. Abstract: Objective: Preexisting diabetes in pregnancy is associated with a high risk of emergency cesarean section (CS), which is associated with increased risk of maternal and neonatal complications. Thus, the aim of this study was to identify possible predictors of emergency CS in women with preexisting diabetes. Study design: This is a secondary analysis of a prospective observational study of 204 women with preexisting diabetes (118 with type 1 diabetes and 86 with type 2) with singleton pregnancies recruited at Rigshospitalet, Copenhagen, Denmark from August 2015 to February 2018. Mode of delivery (trial of labor or planned CS) was individually planned in late pregnancy based on clinical variables reflecting maternal and fetal health including glycemic control and ultrasonically estimated fetal weight. Univariate and multivariable analyses were performed to identify possible predictors of in labor emergency CS. Results: Trial of labor was planned in 79 % (n = 162) of the women of whom 65 % (n = 105) were delivered vaginally and 35 % (n = 57) by an emergency CS, while the remaining 21 % (n = 42) were offered a planned CS. Nulliparity (adjusted odds ratio (aOR) 5.6 95 % CI 1.7–18.8), presence of a hypertensive disorder (aOR 2.8, 95 % CI 1.2–6.7) and previous CS (aOR 6.7, 95 % CI 1.5–28.9) were independently associated with an emergency CS. Maternal height was inversely associated with emergency CS (aOR 0.6 95 %, CI 0.5-0.9 per 5 cm decrease). Neither maternal HbA1c nor ultrasonically estimated fetal size in late pregnancy were associated with emergency CS. Women scheduled for a planned CS were characterized by poorer glycemic control and higher estimated fetal size than those offered a trial of labor. Conclusion: Nulliparity, presence of a hypertensive disorder, previous CS and shorter maternal height were predictors of emergency CS in women with a planned trial of labor, whereas this not was the case for late pregnancy maternal Hba1c or fetal size estimated by ultrasound.